Introducing psychology - Benson, Nigel C. (Thirplow, Cambridge [England] : Totem Books, 2007)
Discusses the basic principles and main theories of psychology, with illustrations, covering various schools of thought, such as behaviorism, social psychology, and humanism, and key figures such as Jung, Pavlov, Maslow, Skinner, and Piaget.
Includes bibliographical references (p. [173-174]) and index.
Young Adult
Young Adult
Keywords: Psychology -- Comic books, strips, etc; Comic books, strips, etc; Psychology -- Comic books, strips, etc